Optimal Cash Ratio and Adjustment Speed Across Different Firm Characteristics - Otaify, Mahmoud; Dawood, Aly; Farouk, Mohamed (International Journal of Economics and Financial Issues, 2022)
This paper seeks to use fixed effect and dynamic panel models to examine role of firm characteristics, macroeconomic variables, control of corruption and political uncertainty in explaining cash holdings of Egyptian firms over the period 2011 – 2020. We find that firm characteristics strongly explain variations in corporate cash ratios and deviations from the target ratios. However, we document no considerable role of macro variables. Egyptian firms tend to hold liquid assets as cash substitutes in managing their working capital and use debt as cash substitute in financing their operations. The findings support the prediction of main corporate finance theory and support both the precautionary and transactionary motives to hold cash. As expected, Egyptian firms tend to hold more cash during periods of high political uncertainty. After sorting according to the most influential independent variables which are tangibility and dividend yield (high and low). We find that cash holdings of the firms respond differently to both the firm specific variables and macro variables. Specifically, the high tangibility firms adjust their cash holding to the optimal level faster than the low tangibility firms while the low dividend yield firms adjust faster than the high dividend yield firms. The results of dynamic panel models indicate that Egyptian firms follow a partial adjustment policy towards the optimal cash levels, which corresponds with trade off theory.